Priority for one's own stimulus in joint performance: evidence from an event-related potential study. Issue 8 (25th May 2016) - Kato, Kimiko; Yoshizaki, Kazuhito; Kimura, Yumi
Abstract : To investigate priority of shared task representations (own vs. other) formed during joint task performance, event-related potentials were recorded while participants performed an auditory three-stimulus oddball task alone (individual condition) and with another participant (joint condition). Participants were required to discriminate between frequent standard tones and rare target tones, while ignoring nontargets assigned to a partner's action (i.e. no-go stimuli for one's own task performance). The parietal P3b was elicited for targets under both conditions. In contrast, P3b for nontargets was observed only in the joint condition, and in addition, it accompanied the frontal no-go P3. This implies that coactors share one another's task representations. Importantly, the emergence of P3b and no-go P3 for nontargets was delayed compared with P3b for targets, suggesting that shared task representations are serially applied to the stimulus processing and that one's own representations precede the other individual's representations.